2017
DOI: 10.1094/phyto-07-16-0280-r
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Pathogen Verticillium longisporum Does Not Affect Water Relations and Plant Responses to Drought Stress of Its Host, Brassica napus

Abstract: Verticillium longisporum is a host-specific vascular pathogen of oilseed rape (Brassica napus L.) that causes economic crop losses by impairing plant growth and inducing premature senescence. This study investigates whether plant damage through Verticillium stem striping is due to impaired plant water relations, whether V. longisporum affects responses of a susceptible B. napus variety to drought stress, and whether drought stress, in turn, affects plant responses to V. longisporum. Two-factorial experiments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The increase in ABA in the leaves of oilseed rape and Arabidopsis likely results from side effects, provoked by the fungal invasion into the roots and growth in the xylem, which could lead to an initially reduced water supply within the leaves. However, Reusche et al () reported that at 7 dpi V. longisporum triggers de novo xylem formation that can compensate for compromised water transport in brassicaceous host plants, which can explain why this vascular pathogen does not affect drought stress responses in oilseed rape (Lopisso et al , ). Furthermore, the increased ABA levels in Arabidopsis might contribute to an increased drought stress tolerance that has been observed for V. longisporum ‐infected plants (Reusche et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in ABA in the leaves of oilseed rape and Arabidopsis likely results from side effects, provoked by the fungal invasion into the roots and growth in the xylem, which could lead to an initially reduced water supply within the leaves. However, Reusche et al () reported that at 7 dpi V. longisporum triggers de novo xylem formation that can compensate for compromised water transport in brassicaceous host plants, which can explain why this vascular pathogen does not affect drought stress responses in oilseed rape (Lopisso et al , ). Furthermore, the increased ABA levels in Arabidopsis might contribute to an increased drought stress tolerance that has been observed for V. longisporum ‐infected plants (Reusche et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rainfall was over twice as much during Verticillium stem striping, and further research is needed to reveal putative relations on the yield impact of this disease. However, watering regimes were previously shown not to impact V. longisporum disease levels if grown under controlled greenhouse conditions (Lopisso et al, 2017b).…”
Section: Discussionmentioning
confidence: 98%
“…In order to detect an infection with V. longisporum, the DNA content of the pathogen was carried out using qPCR analysis (Table 1). In case of artificial inoculation under laboratory conditions, there is no resting phase for the host plant as well as for the fungus, therefore colonization of the vascular system is probably more rapid [52] and disease symptoms are different compared to plants growing in field conditions [53]. Using the entire plant (without roots) shows a more realistic picture of the state of infection of B. napus compared to analysis of only the hypocotyls of the plant.…”
Section: Discussionmentioning
confidence: 99%